Sistem Monitoring Beban Trafo Distribusi Secara Visual Dan Sms Gateway di PT PLN (Persero) - Musthofa Musthofa; Ujang Nur Rahman (Energi & Kelistrikan, 2021)
Economic growth of the community encourages the increasing electricity demand. To meet the electricity demand, of course, it is necessary to increase the capacity of the distribution transformer with the addition of an insert transformer and a new transformer. So that the increasing number of installed transformers is not proportional to the number of officers measuring the transformer load. The problem is the number of transformers is 3,938 units at PLN UP3 Padang with only 70 teams of load measuring officers, so load measurement only reaches 68% in 2019. This is because load measurements are carried out manually by mandating substations one by one, thus requiring large human resources and costs. Under these conditions, an easy and fast load measurement monitoring system is needed. This study uses the Root Cause Problem Solving (RCPS) methodology and System and Equipment Design by creating a Visual Transformer Load Monitoring System and SMS Gateway. With this system and equipment, the load of the substation can be easily seen visually with a light indicator installed on the panel box of the substation pole, so that the condition of the transformer can be quickly identified. The telemetering function with SMS sends load data to officers so that the risk of transformer damage can be reduced because this tool is an early warning against unbalanced loads, one phase outages with the Condition Base Maintenance (CBM) principle so that PLN can maintain transformer lifetime and maintain service quality. Keywords: Load Monitor, Visual and SMS Gateway, Distribution Transformer